Floral anatomy of Thomandersia (Lamiales), with particular reference to the nature of the retinaculum and extranuptial nectaries - Wortley, A; Scotland, R; Rudall, P (2005)
Thomandersia is an isolated genus that is currently unplaced in Lamiales. In the past it has been classified in Acanthaceae or Pedaliaceae, on the basis of intuitive assessments of a limited number of morphological characters. Recent molecular sequenced-based phylogenies have suggested a relationship to Bignoniaceae, Schlegeliaceae or Verbenaceae. Here we present new observations of the floral anatomy of Thomandersia, with particular emphasis on the structure of the retinaculum, a character shared with Acanthaceae, and calyx nectaries, which may be shared with other families in Lamiales. The morphological and anatomical characters of Thomandersia are discussed in the context of recent phylogenetic hypotheses for Lamiales, with the aim of identifying potential primary and secondary homologies between Thomandersia and related families in Lamiales. We find that Thomandersia shares a range of characters with each of the families to which it might be sister-group, and that some of these primary homologies must therefore be homoplastic. In particular, if the topology based on molecular sequence data is correct, the retinacula of Thomandersia and Acanthaceae are homoplastic and represent an example of parallel morphological evolution. © 2005 The Linnean Society of London.